Pre-travel malaria enquiries to the United Kingdom national travel advice line 2016: Advice mainly needed on malaria maps and risk groups. Issue 30 (July 2019) - Kay, Natasha; Ive, Louisa; Petersen, Jakob; Kanagarajah, Sanch; Simons, Hilary; Patel, Dipti
Abstract: Background: Malaria prevention in travellers can be complex and requires consideration of a number of factors. UK healthcare professionals providing pre-travel malaria advice can access specialist support from the National Travel Health Network and Centre (NaTHNaC) telephone advice line. The aim of this study is to characterise queries to the NaTHNaC telephone advice line regarding pre-travel malaria advice. Method: Telephone calls received to NaTHNaC's advice line are recorded using an online data capture form. All calls relating to malaria advice during 2016 were selected and data extracted. Analysis was undertaken using Microsoft Excel and STATA. Results: During 2016, 1803 malaria-related calls were received; the majority from general practice and calls were from across the UK. The most common type of pre-travel malaria query was country-specific followed by travellers with special health needs. Many queries related to pregnant and breastfeeding travellers, children under 5 years and travellers over 60 years. Conclusions: This review presents a large and exceptional dataset and reflects the ambiguity amongst some healthcare professionals regarding malaria advice. We have identified potential knowledge gaps, and as a result will strengthen future guidance, enhance existing malaria maps, and inform the development of future clinical educational activity.